The Incidence of Graft on Developing-Country Firms - González, Alvaro; Ernesto López-Córdova, J.; E. Valladares, Elio (World Bank, Washington, DC, 2012)
This paper measures the extent to which firms in developing countries are the target of bribes. Using new firm-level survey data from 33 African and Latin American countries, we first show that perceptions adjust slowly to firms' experience with corrupt officials and hence are an imperfect proxy for the true incidence of graft. We then construct an experience-based index that reflects the probability that a firm will be asked for a bribe in order to complete a specified set of business transactions. On average, African firms are three times as likely to be asked for bribes as are firms in Latin America, although there is substantial variation within each region. Last, we show that graft appears to be more prevalent in countries with excessive regulation and where democracy is weak. In particular, our results suggest that the incidence of graft in Africa would fall by approximately 85 percent if countries in the region had levels of democracy and regulation similar to those that exist in Latin America.